Proyectos de ley presentados por el Gobierno Nacional a la consideración del Congreso : en sus sesiones ordinarias de 1947 (Imprenta Nacional, 1947)
Bills proposed by various ministries of the Colombian government for legislative action during the 1947 sessions. The tables of contents group the proposed bills by the Ministry putting forward the proposals.